Diversity of Phytoplankton in the Kandis River Karya Indah Village, Tapung Sub-Regency, Kampar Regency, Riau Province - Lusi Vionora; Yuliati '; Efawani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the diversity of phytoplankton in the Kandis River was conducted from January 2014. This research aims to understand the type and abundance of phytoplankton in the Kandis River . There were three stations with 3 sampling points in each station. Samples were taken 3 times, once a week and they were analyzed in the marine productivity Riau University.Result shown that the phytoplankton obtained were consist of 15 species, they were belonged to of 3 classes, namely Chlorophyceae (5 species), Bacillariophyceae (3 species), and Cyanophyceae (7 species). The average of fitoplankton abundance was around 1237-1480 cells/l. General water quality parameters are as follow: temperature: 290C, brightness: 30-32,5 cm, current speed: 0,08-0,12 m/s, pH: 5, DO: 35–3,7 mg/l, CO2: 11,88–12,9 mg/l, nitrate: 0,01–0,2 mg/l and phosphate 0,02–0,23 mg/l. Based on phytoplankton abundance, the Kandis River can be categorized as oligotriphic river.Keywords: Diversity. Phytoplankton, Kandis River